Answer:
a14 = -40,960
Step-by-step explanation:
The sequence has a first term of 5 and a common ratio of -10/5 = -2, so the n-th term is given by ...
an = a1·r^(n-1)
an = 5·(-2)^(n-1)
The 14th term is then ...
a14 = 5·(-2)^(14-1) = -5·2^13 = -5·8192
a14 = -40,960
Answer:
2 7/24
Step-by-step explanation:
1 5/8 + 2/3
1 15/24 + 16/24
1 31/24 = 2 7/24
If my answer is incorrect, pls correct me!
If you like my answer and explanation, mark me as brainliest!
-Chetan K
Answer:
D
Step-by-step explanation:
(2x + 2) -
(3x - 1) = 15
multiply through by 4 ( the LCM of 2 and 4 ) to clear the fractions
2(2x + 2) - (3x - 1) = 60 ← distribute parenthesis and simplify left side
4x + 4 - 3x + 1 = 60
x + 5 = 60 ( subtract 5 from both sides )
x = 55
Answer: 0.0008
Step-by-step explanation: Hope this helps :)
That is your answer if it is wrong i will try to fix it